Characterisation of a public T cell clonotype enriched in m.tb infected individuals who do not progress to tuberculosis - Matela, Motshidisi (Department of Pathology, 2025)
Introduction: T cells are known to play an important role in controlling M. Tuberculosis (M.tb) infection, but it is not known if specific T cell clones contribute to the outcome of M.tb infection. We recently completed a bulk T cell receptor (TCR) sequencing screen and observed that frequencies of a particular donor-unrestricted T cell (DURT) clone were higher in healthy, M.tb infected individuals who controlled infection (controllers), than individuals who progressed to tuberculosis (TB) (progressors). This clone expresses a common complementarity-determining region 3 (CDR3) α sequence, which we termed “kiif.tb”. Frequencies of kiif.tb T cells were also higher in healthy M.tb infected individuals than TB patients in another bulk T cell TCR sequencing screen in a different cohort. Objective: In my project, we aimed to confirm if healthy, M.tb infected individuals (i.e. IGRA+) have higher frequencies of kiif.tb expressing T cells compared to healthy uninfected individuals (i.e. IGRA-) or individuals with active TB. We also aimed to identify cost-effective methods for detecting kiif.tb T cells in peripheral blood mononuclear cells (pbmcs) and assess the activation phenotype of kiif.tb in IGRA-, IGRA+, and TB patients. Methods: A custom-designed digital PCR (dpcr) assay was used to quantify the frequencies of total T cells and kiif.tb T cells from IGRA-, IGRA+, and TB patients. Identification and characterisation of kiif.tb T cells by flow cytometry was performed using a custom flow cytometry-compatible RNA hybridization assay (primeflowtm) and custom monoclonal antibodies were generated from mice immunised with kiif.tb sequence. Results: Total T cell frequencies measured by dpcr in all participants correlated strongly with both bulk TCR sequencing (rho = 0.74, p-value = 0.02) and flow cytometry (rho = 0.75, p = 5x106). However, the correlation between kiif.tb T cell frequencies measured by dpcr and kiif.tb CDR3a measured using bulk TCR sequencing was modest (rho = 0.48, p-value = 0.01). Kiif.tb T cell frequencies were not significantly higher in IGRA+ individuals with recent or remote M.tb infection compared to IGRA- controls (p = 0.4 and 0.31, respectively), nor when compared to individuals with TB disease (p-value = 0.39 and 0.27, respectively). Frequencies of kiif.tb T cells, quantified by custom monoclonal antibody (clone39a9d4) staining, were not different across study groups. However, active TB patients had higher frequencies of kiif.tb T cells expressing HLA-DR compared to IGRA- controls (p-value = 0.02). We did not include IGRA+ individuals, because only a single individual in this group had sufficient kiif.tb cells for phenotyping. Frequencies of bulk T cells expressing HLA-DR were also higher TB patients than to IGRA+ individuals (p-value = 0.05). Discussion: Our results suggest that kiif.tb-specific T cell frequencies measured by dpcr, or monoclonal antibodies were not different between the clinical groups, contrary to our hypothesis. The custom dpcr assay may only accurately detect targets at higher abundances, like total T cells (30-70%), limiting accuracy for quantifying kiif.tb T cells, which occur at abundances 1000-fold lower (0-0.04%). Next steps involve validating initial findings using bulk TCR sequencing and further optimizing the monoclonal antibody staining for kiif.tb T cell quantification by flow cytometry. Notably, our HLA-DR data suggest that kiif.tb T cells are highly activated in patients with active TB, which may suggest that these DURT cells recognise M.tb antigen. With further optimization, such an antibody could useful for developing novel T-cell-based TB biomarkers